The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyt.2021.705998
|View full text |Cite
|
Sign up to set email alerts
|

Common and Distinct Alterations of Cognitive Function and Brain Structure in Schizophrenia and Major Depressive Disorder: A Pilot Study

Abstract: Objective: Numerous studies indicate that schizophrenia (SCZ) and major depressive disorder (MDD) share pathophysiological characteristics. Investigating the neurobiological features of psychiatric-affective disorders may facilitate the diagnosis of psychiatric disorders. Hence, we aimed to explore whether patients with SCZ and patients with MDD had the similar or distinct cognitive impairments and GMV alterations to further understand their underlying pathophysiological mechanisms.Methods: We recruited a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
2
2
0
Order By: Relevance
“…Therefore, it is not surprising that cognitive impairments are a common endophenotype in both illnesses, and the results of the present study lend support to this conclusion. A previous study reported similar cognitive abnormalities in relation to information processing speed and similar reductions in the gray matter volume in the right medial superior frontal cortex associated with executive functions between patients with schizophrenia and major depressive disorder [81]. These results could be consistent with our finding of the absence of any difference in the subjective difficulty with Planning/Organization as assessed by the PDQ, which is thought to reflect executive functions, between patients with schizophrenia spectrum disorders and major depressive disorder in the present study.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, it is not surprising that cognitive impairments are a common endophenotype in both illnesses, and the results of the present study lend support to this conclusion. A previous study reported similar cognitive abnormalities in relation to information processing speed and similar reductions in the gray matter volume in the right medial superior frontal cortex associated with executive functions between patients with schizophrenia and major depressive disorder [81]. These results could be consistent with our finding of the absence of any difference in the subjective difficulty with Planning/Organization as assessed by the PDQ, which is thought to reflect executive functions, between patients with schizophrenia spectrum disorders and major depressive disorder in the present study.…”
Section: Discussionsupporting
confidence: 53%
“…Not only do schizophrenia and major depressive disorder share common symptoms, they also reportedly share a common genetic background [61][62][63]. Therefore, it is not surprising that cognitive impairments are a common endophenotype for both illnesses [64], and the results of the present study support this conclusion. This commonality may be applicable not only to major depressive disorder and schizophrenia, but also to various other mental illnesses.…”
Section: Discussionsupporting
confidence: 78%
“…Several previous studies have used the MCCB to evaluate the levels of cognition in patients with schizophrenia due to its ideally psychometric properties (27,(66)(67)(68). In the past decades, many studies used MCCB to investigate the relationship between the cognitive performance and brain structural and functional alterations in the patients with schizophrenia (69)(70)(71)(72)(73)(74)(75) (64,66). GDS method can be described briefly as follows: demographically corrected T-scores were converted to deficit scores according to the following criteria: T > 39 = 0 (normal), 39 ≥ T ≥ 35 = 1 (mild impairment), 34 ≥ T ≥ 30 = 2 (mild to moderate impairment), 29 ≥ T ≥ 25 = 3 (moderate impairment), 24 ≥ T ≥ 20 = 4 (moderate to severe impairment), T < 20 = 5 (severe impairment).…”
Section: Participants and Proceduresmentioning
confidence: 99%